Manajemen Pendidik Dalam Mengembangkan Bahasa Melalui Media Buku Cerita Bergambar Di Paud Anak Negeri - eliyana, eliyana; Ramzi, Muhajirin; Nursofiza, Nursofiza (Lembaga Penelitian dan Pendidikan Mandala, 2023)
One aspect of child development that must develop is language development, so that children are able to communicate well in their social environment, training children to speak can improve communication and speak better, at an early age, the development is very good and it is very important for a teacher to stimulate child development to develop well, the role of a teacher or educator is very important in PAUD Anak Negeri. Educators who promote children's language development through picture book media and so-called